A High-Performance Liquid Chromatography- Tandem Mass Spectrometry- Based Targeted Metabolomics Kidney Dysfunction Marker Panel in Human Urine - Klepacki, Jacek (Clin Chim Acta, 2015)
BACKGROUND: Previous studies have examined and documented fluctuations in urine metabolites in response to disease processes and drug toxicity affecting glomerular filtration, tubule cell metabolism, reabsorption, oxidative stress, purine degradation, active secretion and kidney amino acylase activity representative of diminished renal function. However, a high-throughput assay that incorporates metabolites that are surrogate markers for such changes into a kidney dysfunction panel has yet to be described. METHODS: A high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) assay for the quantification of ten metabolites associated with the Krebs cycle, purine degradation, and oxidative stress in human urine was developed and validated. Normal values were assessed in healthy adult (n=120) and pediatric (n=36) individuals. In addition, 9 pediatric renal transplant recipients patients were evaluated before and after initial dosing of the immunosuppressant tacrolimus in a proof-of-concept study. RESULTS: The assay met all predefined acceptance criteria. The lower limit of quantification ranged from 0.1 to 1000 µmol/l. Inter-day trueness and imprecisions ranged from 91.4–112.9% and 1.5–12.4%, respectively. The total assay run time was 5.5 minutes. Concentrations of glucose, sorbitol, and trimethylamine oxide (TMAO) were elevated in pediatric renal transplant patients (n=9) prior to transplantation as well as before and immediately after initial dosing of tacrolimus. One month post-transplant urine metabolite patterns matched those of healthy children (n=36). CONCLUSIONS: The LC-MS/MS assay will provide the basis for further large-scale clinical studies to explore these analytes as molecular markers for the patients with renal insufficiency.